Chronic Disorders in Children and Adolescents - Goldstein, Mark L.; Morewitz, Stephen J. (Springer New York : Imprint: Springer, 2011)
The rising number of children and adolescents with chronic conditions comprises one of the most significant challenges in health care today-one that needs to be met with tailored research studies, earlier assessment, age-appropriate prevention efforts, effective, targeted treatment, improved compliance strategies, and proactive involvement by family members. Chronic Disorders in Children and Adolescents was written in line with these critical goals, providing an epidemiology of major chronic diseases among children and youth (and not only the prevalence of disorders and their risk factors, but also their burden on health care systems) as well as case studies illustrating psychosocial issues associated with long-term illness in young people. For thirteen frequently encountered conditions-chromosomal abnormalities, autism, cerebral palsy, attention-deficit hyperactivity disorder, sensory integration dysfunction, conduct and oppositional defiant disorders, depressive disorders, eating disorders, childhood and adolescent obesity, diabetes mellitus, juvenile arthritis, and HIV/AIDS-the book focuses on these crucial areas: Current findings on medical and mental health complications Impact on disability and psychosocial development Latest trends in diagnostic, treatment, and rehabilitative strategies The roles of family, peers, school, and others in coping and support New directions in patient education and self-management Given the scope of its knowledge, Chronic Disorders in Children and Adolescents will be a go-to resource for a wide range of professionals and students across pediatrics, medicine, nursing, public health, mental health, education, health administration and policy, social work, and the social sciences.